STRATEGI PENGUATAN NILAI-NILAI BUDAYA SEKOLAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SMP NEGERI 33 MAKASSAR - Yulianty, Astri; Basri, Syamsurijal; Habibah, Sitti (Irfani, 2025)
Strengthening Strategy of School Cultural Values in Improving the Quality of Education at SMP Negeri 33 Makassar. The focus of this research is (1) Strengthening Strategy of School Cultural Values, (2) Supporting & Inhibiting Factors. The purpose of this research is to identify and analyze the values and strategies applied, as well as the supporting and inhibiting factors in their implementation. This research approach is qualitative with descriptive research type. The research data sources are the Principal, Vice Principal, and Teachers. The data collection procedures used are interviews, observation and documentation. Checking the validity of the data uses the triangulation method, data analysis is carried out by data reduction, data presentation to drawing conclusions. The results of the research show that (1) Strengthening strategy of values is through (a) Establishing shared norms, (b) Effective communication between school residents, (c) Leadership oriented towards cultural values, (d) Policies that support a positive culture. (2) Supporting & Inhibiting Factors (a) Supporting factors include leadership, teacher cooperation, parental participation, and good communication that strengthen school culture. (b) Inhibiting factors include miscommunication, lack of understanding of cultural values, and low teacher discipline that require coaching. Overall, the strategy for strengthening school cultural values is carried out systematically by strengthening values through shared norms, effective communication, value-based leadership, and positive policies. In implementing this strategy, it can strengthen the values of discipline, integrity, mutual cooperation, nationalism, creativity, and innovation. The main supporting factors include the role of the principal, teacher cooperation, and parental participation, while the obstacles are miscommunication, low cultural understanding, and lack of teacher discipline.